Detection of 20ph+ in a woman with idiopathic recurrent pregnancy loss - Banerjee, Byapti; Ganguly, Chandrima; Chatterjee, Sukanta; Kumar Saha, Ashis; Dutta, Atreyee (Indian Journal of Case Reports, 2026)
Recurrent pregnancy loss (RPL) constitutes a multifactorial clinical entity, often necessitating an exhaustive diagnostic approach when routine investigations yield inconclusive results. We report the case of a 23-year-old female with two consecutive unexplained pregnancy losses, in whom comprehensive endocrine, thrombophilia, and radiological evaluations were unremarkable. However, cytogenetic analysis revealed a rare heterochromatic variant, 20ph+, in the female partner, whereas the male partner’s karyotype was normal. Although 20ph+ is typically regarded as a benign chromosomal polymorphism, its infrequent occurrence and detection in reproductive disorders invite reconsideration of its potential clinical significance. To our knowledge, this is the first study in India to report the presence of 20ph+ in the context of RPL. This case study underscores the importance of incorporating cytogenetic analysis into the diagnostic workup for idiopathic RPL, especially when standard investigations fail to identify a cause.